2017
DOI: 10.2147/oajsm.s131596
|View full text |Cite
|
Sign up to set email alerts
|

High lateral plantar pressure is related to an increased tibialis anterior/fibularis longus activity ratio in patients with recurrent lateral ankle sprain

Abstract: IntroductionCenter of pressure (COP) is a sudden displacement at the time of a lateral ankle sprain (LAS). It has been suggested that the distribution of plantar pressure and the quantity of COP displacement are important for assessing the risk of LAS. Therefore, we evaluated the plantar pressure during a single-leg balance test with eyes closed (SLB-C) to identify the factors and characteristics of plantar pressure in people with repeated cases of LAS.MethodsWe recruited 22 collegiate athletes and divided the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…As a result, it is presumed that this causes compensatory movement occurring in the direction of the ankle flexors. A previous study showed that a patient with a history of ankle joint sprains has an outsole load during gait or one-leg standing 23) . In the current study, we infer that it is difficult for our participants to similarly load on their toe side.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is presumed that this causes compensatory movement occurring in the direction of the ankle flexors. A previous study showed that a patient with a history of ankle joint sprains has an outsole load during gait or one-leg standing 23) . In the current study, we infer that it is difficult for our participants to similarly load on their toe side.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the value of the leg-heel angle increased after the PHVA, indicating that the foot was close to inversion. Previous studies showed that patients with CAI are more laterally loaded than healthy subjects 21 and that they exhibit reduced lateral support alignment. 33,34 In the present study, leg-heel angle on weight-bearing during the PHVA phase showed a similar eversion angle to that of adults in the post-PHVA phase.…”
Section: Discussionmentioning
confidence: 97%
“…A lateral shift in foot pressure distribution has also been identified as a risk factor for the onset of LAS based on kinetic and kinematics data. 21 To our knowledge, prospective research has yet to be conducted to evaluate whether these risk factors also make the pediatric and adolescent athlete more prone to LAS.…”
Section: Introductionmentioning
confidence: 99%
“…The function of the peroneus longus immediately before impact is important since the muscle should respond effectively to the inversion moment of the ankle as the foot impacts the ground [ 42 ]. A high activation level of the ankle evertor is essential in protecting the ankle at impact [ 43 ]. However, a flattening of the medial longitudinal arch occurs on contact, and thus the ankle invertor muscles (e.g., the tibialis anterior) eccentrically contract in order to control the foot and ankle complex.…”
Section: Discussionmentioning
confidence: 99%